Comparison of the Effectiveness of Blended Project-Based Learning and Project-Based Learning Strategies on Chemistry Concept Understanding - Willy agustina Bangun; Alfiati Hasanah; Ririn Ningkeula (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2026)
Given technological advancements, innovation is required to better tailor project-based learning to students who are predominantly